(untitled) (Bangladesh Journal of Agricultural Research, 2026)
The field experiment was carried out at Regional Agricultural Research Station, Bangladesh Agricultural Research Institute, Rahmatpur, Barishal during two consecutive Rabi seasons of 2019-2020 (Y1) and 2020-2021 (Y2) to develop nutrient management package for mustard as relay crop with T.aman rice for higher yield and economic return of the crop under Ganges Tidal Floodplain. The treatments of the experiment were: T1 = 100% Recommended dose (RD: 90-27-16-15-1.5-1-1 kg/ha N-P-K-S-Mg-Zn-B), T2 = 75% of RD, T3 = 50% of RD, T4 = 25% of RD, and T5 =(72-22-13-12-1.5-0.8-0.8 kg/ha N-P-K-S-Mg-Zn-B, respectively) on soil test based (STB).. Fertilizer dose for previous T. aman rice was: 75-10-18-4-1 kg/ha N-P-K-S-Zn, respectively. The variety of mustard was BARI Sarisha-14. The experiment was laid out in a randomized complete block design with three replications. The experimental results revealed that nutrient management packages had significant effect on plant height, number of siliqua/plant, seed yield and straw yield in Y1. On the other hand, in Y2, number of siliqua /plant, number of seed/siliqua, seed yield and straw yield differed significantly by the nutrient packages. The maximum seed yield was obtained from T1 treatment (1235 kg/ha) in Y1, which was at par to that of T2 (1183 kg/ha) and T5 (1112 kg/ha), respectively. In Y2, the maximum seed yield was found in T2 (1228 kg/ha) that was statistically at par to that of T1 (1225 kg/ha) and T5 treatment (1189 kg/ha). The results further revealed that 75 - 100% RD of fertilizers as well as soil test based (STB) fertilizer dose gave similar seed yield. The fertilizers applied in previous T.aman rice had residual effect in succeeding mustard crop. Therefore, application of 75% RD or STB fertilizer dose along with residual fertilizer nutrients produced almost higher yield as per full dose of fertilizers. In average of two years, the highest gross return (Tk. 82524 /ha) and total variable cost (Tk. 53643/ha) were found in treatment T1 (100% RD) but the treatment T2 gave the highest gross margin (Tk. 29354 /ha) with BCR (1.57), which was closely followed by T1 (1.54) and T5 treatments (1.48, respectively). Bangladesh J. Agril. Res. 47(4): 423-431, December 2022